2021
DOI: 10.3390/genes12121932
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Gene Expression Map of Giardia Encystation

Abstract: Giardia intestinalis is an intestinal protozoan parasite that causes diarrheal infections worldwide. A key process to sustain its chain of transmission is the formation of infectious cysts in the encystation process. We combined deep RNAseq of a broad range of encystation timepoints to produce a high-resolution gene expression map of Giardia encystation. This detailed transcriptomic map of encystation confirmed a gradual change of gene expression along the time course of encystation, showing the most significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Genes encoding kinases, regulators of the cell cycle, and arginine metabolism and cytoskeletal proteins were the main down-regulated genes in the interacting trophozoites ( Peirasmaki et al., 2020 ) ( Figure 7 ). This can also be seen in the encysting cells ( Figure 7 and Table S4 ), but the most down-regulated genes in 7 h encysting cells during host cell interactions are up-regulated genes during encystation ( Rojas-López et al., 2021 ); ORFs 5638, 5435, and 2421 cyst wall proteins 1 to 3, 4245 and 11151 hypothetical proteins, 114495 and 137701 NEK kinases, 10552 Ephrin-like receptor, 14626 Oxidoreductase, 112341 Transmembrane protein, 27806 Myb-like protein, 113610 GlcNAc-PI synthesis, and 88581 synaptic glycoprotein ( Table S4 ). This suggests that encysting cells are inhibited in the encystation process during the interaction with Caco-2 cells, and follow-up experiments showed that fewer cysts are produced when 7 h encysting cells are transferred to DMEM or to interacting Caco-2 cells ( Figure S9 ).…”
Section: Resultsmentioning
confidence: 62%
“…Genes encoding kinases, regulators of the cell cycle, and arginine metabolism and cytoskeletal proteins were the main down-regulated genes in the interacting trophozoites ( Peirasmaki et al., 2020 ) ( Figure 7 ). This can also be seen in the encysting cells ( Figure 7 and Table S4 ), but the most down-regulated genes in 7 h encysting cells during host cell interactions are up-regulated genes during encystation ( Rojas-López et al., 2021 ); ORFs 5638, 5435, and 2421 cyst wall proteins 1 to 3, 4245 and 11151 hypothetical proteins, 114495 and 137701 NEK kinases, 10552 Ephrin-like receptor, 14626 Oxidoreductase, 112341 Transmembrane protein, 27806 Myb-like protein, 113610 GlcNAc-PI synthesis, and 88581 synaptic glycoprotein ( Table S4 ). This suggests that encysting cells are inhibited in the encystation process during the interaction with Caco-2 cells, and follow-up experiments showed that fewer cysts are produced when 7 h encysting cells are transferred to DMEM or to interacting Caco-2 cells ( Figure S9 ).…”
Section: Resultsmentioning
confidence: 62%
“…Although reduced encystation efficiency was noted in the M1 and M2 isolates studied here, the underlying molecular rationale is not known as it is still unclear how encystation is initiated at the molecular level ( Rojas-López et al, 2021 ). The encystation process is complex, as evidenced by the extensive and coordinated gene regulatory program that is associated to formation of viable cysts, which holds true for the early part of the process as well ( Rojas-López et al, 2021 ). Thus, the substantial transcriptomic and proteomic changes the parasite needs in order to tolerate MTZ may be in their sum too costly to afford creation of transmission stages.…”
Section: Discussionmentioning
confidence: 79%
“…In the case of G. intestinalis, evolution of MTZ resistance appears to be strongly associated with a significant and multimodal fitness cost (reduced growth rate, attachment, encystation, and animal infectivity), which might explain why it took decades for drug resistance to develop. Although reduced encystation efficiency was noted in the M1 and M2 isolates studied here, the underlying molecular rationale is not known as it is still unclear how encystation is initiated at the molecular level (Rojas-López et al, 2021). The encystation process is complex, as evidenced by the extensive and coordinated gene regulatory program that is associated to formation of viable cysts, which holds true for the early part of the process as well (Rojas-López et al, 2021).…”
Section: Discussionmentioning
confidence: 81%
“…Giardia's cyclin dependent kinase 2 (CDK2) is upregulated at G2+M (46) and has been shown to activate MYB2 through phosphorylation (47). Two recent RNAseq studies also identified an encystation-upregulated cyclin (GL50803_15532) (13) and G2-dependent TF GLP1 (GL50803_7272) (46). In the future, it would be interesting to explore how GLP1, GLP4, CDK2, and cyclin work together to initiate encystation.…”
Section: Discussionmentioning
confidence: 99%
“…Giardia's cyst wall is composed of 37% cyst wall proteins (CWPs) and 63% carbohydrate filaments which are mainly made up by a [D-GalNAc-β(1-3)-D-GalNAc] n homopolymer (10)(11)(12). The expression levels of CWP1-3 are upregulated at 2-4 h post induction of encystation (13)(14)(15). The enzymes involved in the synthesis of β(1-3) GalNAc homopolymer, including GlcN 6-P isomerase (G6PI-B), GlcN 6-P N-acetylase (GNPNAT), phosphoacetylglucosamine mutase (PGM), UDP-GlcNAc pyrophosphorylase (UAP), UDP-GlcNAc 4'-epimerase (UAE) are upregulated at 10-18h post induction of encystation (10,11,13,15).…”
Section: Introductionmentioning
confidence: 99%